Laboratory and field tests of predation on the cereal leaf beetle, Oulema melanopus (Coleoptera: Chrysomelidae). Issue 5 (4th May 2019) - Kheirodin, Arash; Costamagna, Alejandro C.; Cárcamo, Héctor A.
ABSTRACT: The cereal leaf beetle (CLB), Oulema melanopus (L.) (Coleoptera: Chrysomelidae), is an invasive pest in North America recently reported in the Canadian Prairies. We performed a series of laboratory assays to identify potential predators and a field study to quantify predation of CLB eggs. In no-choice Petri dish assays, ground beetles (Carabidae), rove beetles (Staphylinidae), and several common lady beetle species (Coccinellidae) were the most consistent predators of eggs and larvae. Nabis spp. (Hemiptera: Nabidae) and wolf spiders (Araneae: Lycosidae) consumed many larvae, but did not consume eggs. Hippodamia spp., Coccinella septempunctata (L.) (Coleoptera: Coccinellidae), and Pterostichus melanarius (Illiger) (Coleoptera: Carabidae) also fed on CLB eggs on potted plants when an alternative food source was available, Sitobion avenae (Fabricius) (Hemiptera: Aphididae). In our field study, we found an average of 24.5% of sentinel eggs disappeared over a 24 h period, likely due to predation. Our results suggest that generalist predators can play an important role in the biological control of CLB, and warrant further study.